Os espelhos dos rios: dimensões simbólicas da relação de gênero na lenda Amazônica o Boto - Magalhães, Gilzete Passos (2013)
Analytical Psychology believes that psychological aspects are also expressed through myths, folklore, fairy tales and historical-cultural processes. Seeking to grasp these phenomena, it promotes dialogues with various areas of knowledge. This research aims to understand The River Dolphin legend under the symbolic viewpoint and its significance to masculinity, femininity and gender relations in some groups of riverside communities in the Amazon Region. For this study, we adopted the qualitative method of analysis by means of a documentary research from which we selected narratives about this folklorical character in literature, music, film, and the testimonials of people from coastal communities compiled by scholars in History, Anthropology, Music and Analytical Psychology. The chosen material was submitted to the archetypal symbolic processing (PENNA, 2009) that proposes the understanding of the symbol meaning, and from this research stage onwards we identified three thematic groups for analysis: the symbolism of nature in The River Dolphin legend, the dynamics of the psyche in gender relations in riverine communities, and The River Dolphin and its reflection in the myths. The results of the study suggest the influence of geographical and cultural aspects in the riverine imagery, also indicating that The River Dolphin legend deals with themes that could lead to defensive separation of male and female in the constitution of genres and their relationship